Gold-catalyzed cyclization of nonterminal propargylic amides to substituted alkylideneoxazolines and -oxazines - Hashmi, A. Stephen K.; Schuster, Andreas M.; Schmuck, Martin; Rominger, Frank (European journal of organic chemistry, 2011)
The substrate scope of the gold-catalyzed cyclization of nonterminal propargylic amides to oxazolines and oxazines was investigated. Sixteen alkyl-substituted and 35 aryl-substited substrates were prepared by a very variable route from trimethylsilyl-(TMS-)protected, nonterminal propargylamines. Steric and electronic influences of the substituents on product selectivity were studied. A chloromethyl substituent on the alkyne shows an efficient 1,4-elimination to deliver vinyloxazoles. A second alkynyl group, tethered to the alkyl group at the alkyne, in some cases led to a gold catalysis/Alder-ene domino reaction. With Barluenga's reagent the iodoalkylideneoxazoline can be formed in excellent yield. In contrast to the palladium-catalyzed protocols, the gold-catalyzed conditions for the cyclization of nonterminal propargylic amides are much milder, thus, for example, no special precautions are needed to prevent isomerization of the oxazolines to the aromatic oxazoles.